30.9k views
4 votes
David performed the following mathematical operation:2x+3x+3)2x2 +93 +9He was left with a remainder of zero. Which of the following statements mustbe true?

David performed the following mathematical operation:2x+3x+3)2x2 +93 +9He was left-example-1
User Meet Doshi
by
4.7k points

1 Answer

1 vote

\begin{gathered} from_{\text{ }}x+3 \\ \to x+3=0 \\ solve_{\text{ }}for_{\text{ }}x\colon \\ x=-3 \\ evaluate_{\text{ }}the_{\text{ }}polynomia_{\text{ }}for_{\text{ }}x=-3 \\ 2(-3)^2+9(-3)+9=18-27+9=0 \end{gathered}

Therefore, -3 must be a root of the polynomial 2x²+9x+9

User Narendranath Reddy
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.